IL7R Is Correlated With Immune Cell Infiltration in the Tumor Microenvironment of Lung Adenocarcinoma - Wang, Xin; Chang, Shujian; Wang, Teng; Wu, Ruirong; Huang, Zebo; Sun, Junjie; Liu, Jingjing; Yu, Yan; Mao, Yong (Frontiers in Pharmacology, 2022)
Tumor microenvironment plays an important role in the development, progression, and prognosis of lung adenocarcinoma. Exploring new biomarkers based on the immune microenvironment of lung adenocarcinoma can effectively predict the prognosis and provide effective clinical treatment. In this study, we used the ESTIMATE algorithm to score the immune and stromal components in lung adenocarcinoma data downloaded from the TCGA database. The result showed that the immune/stromal score was associated with clinical features and prognosis of lung adenocarcinoma patients. Interleukin-7 receptor (IL7R) is an important prognostic biomarker identified by intersection analysis of protein-protein interaction networks and Cox regression survival analysis. According to TCGA and Oncomine database analysis, IL7R expression in adenocarcinoma tissues was significantly lower than that in normal lung tissues and was further verified in clinical tissue samples. Survival analysis showed IL7R was an independent prognostic factor of lung adenocarcinoma. IL7R expression was positively correlated with the overall survival and progression-free survival of lung adenocarcinoma patients and negatively correlated with tumor size. Our results suggest that IL7R inhibits tumor growth by regulating the proportion of immune infiltrating cells in the tumor immune microenvironment. IL7R could be a beneficial prognostic marker in patients with lung adenocarcinoma and has great potential in immune therapy.